ANALISIS TEKNIS DAN FINANSIAL SISTEM PENYIMPANAN GABAH DI SUMATERA SELATAN - Ervan Dinata Ginting; Amin Rejo; Tamaria Panggabean (Universitas Sriwijaya, 2012)
This research objective was to analysis the technical and financial variety of grain storage systems in South Sumatra. This study used description method through observation and the data analysis the technical and financial. The Hermetic storage system of puddy grain have a theoritical capacity (KT) was 70 kg, the effective capacity (KE) was 50 kg, the efficiency of equipment (EA) was 71.42%, depreciation of puddy grain 6%, BEP price production was Rp 3.557/kg, BEP for volume production 1.253,74 kg, NPV Rp. 2.420.893, Net B/C ratio 1.18 and IRR 53%. The barn system have KT was 768.000 kg, KE was 200.000 kg, EA was 26,04%, depreciation of puddy grain 18%, BEP price production was Rp 3.048/kg, BEP for volume production 124.976,10 kg, NPV Rp. 433.782.041, Net B/C ratio 1,31 and IRR 51%. The rice plant system have KT was 1.024.000 kg, KE was 700.000 kg, EA was 68,36%, depreciation of puddy grain 18%, BEP price production was Rp 2.889/kg, BEP for volume production 414.525,51 kg, NPV Rp. 1.784.722.815, Net B/C ratio 1,33 dan IRR 56,06%. The sacks system have KT was 25 kg, KE was 20 kg, EA was 80%, depreciation of puddy grain was 10%, BEP price production was Rp 3.583/kg, BEP for volume production 145,11 kg, NPV Rp. 240.005, Net B/C ratio 1,14 dan IRR 55,65%. Based on the investment criteria of sensitivity analysis increased the cost of 10%, and sensitivity analysis of decrease the prices of 10% of storage systems still fit for use because NPV > 0 and Net B/C ratio > 1. Keywords : Technical analysis, analysis of financial, analysis of sensitivity